Perancangan Sistem Aplikasi MATIF Sebagai Media Informasi Dan Kreativitas Di Universitas Katolik Santo Thomas - Andrew Jonatan Damanik; Bendri Sepriadi Zeremia Ambarita; Hardiman Ruhut Simamora; Ishak Eben Haezer Pasaribu (Unit Pengelola Jurnal Universitas Harapan Medan, 2023)
As time goes by, technology is evolving. The trends and interests of people also follow these technological developments. For example, now more and more mobile applications are developed by companies for people to use. The most widely used mobile applications are usually android-based compared to iOS-based. This is because android-based smartphones are more affordable. The purpose of this research is to design an application, we call MaTif (Creative Student) which is used as a medium for students of Universitas Katolik Santo Thomas to share information on campus. This application also aims to be used by students of the Universitas Katolik Santo Thomasto channel their creativity. This application will be built for devices based on the Android operating system. This research is important because the information and creativity of Universitas Katolik Santo Thomas students will be contained in this application and can help other students on campus to get information and also be inspired by the creativity of other students